TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP DATA KONSUMEN PENGGUNA APLIKASI PINJAMAN ONLINE LEGAL (STUDI KASUS PADA APLIKASI PINJAMAN ONLINE ADAKAMI) - Wulan Ndari, Mita; Saputra, Arikha (Jurnal Media Justitia Nusantara, 2023)
One of the online loan applications that is being studied in this research is the AdaKami application. AdaKami is a local online peer-to-peer lending platform that provides loan (credit) facilities without collateral, this requires a study of legal protection from AdaKami for application users and must be reviewed from a positive legal perspective in Indonesia. There are two objectives of this research, namely exploring legal protection for users in the AdaKami online loan application and a positive legal review of the legal protection of users of online loan applications. This type of research is doctrinal/normative law research. Where this research is focused on examining the application of the rules or norms in positive law. The results of the study show that AdaKami does not disseminate data outside of emergency contacts and is subject to statutory regulations, then the protection that can be provided according to positive law is preventive and repressive.